ENERGY DEMAND FORECAST FOR TURKISH AGRICULTURE SECTOR: GRANGER CAUSALITY AND COINTEGRATION TEST - Mehmet Arif ŞAHİNLİ; Ahmet ÖZÇELİK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Due to the fact that, Turkey is a importing energy, we must determine the energy needs in the Turkish agricultural sector. In this study, consumed energy data in agriculture was used between 1972 and 2015 years. According to Turkish Statistical Institute’s database, agriculture sector shares in GDP 6.2 percent in 2016 and percentage change compared to same period in previous year -0.1 percent. Agriculture sector shares in GDP 6.1 percent in 2017 and percentage change compared to same period in previous year 17.2 percent. Gross domestic product increased by 5.2% compared with the same quarter of the previous year in the second quarter of 2018. When the activities which constitute gross domestic product were analysed the total value added decreased by 1.5% in the agricultural sector compared with the same quarter of the previous year in the chained linked volume index. Trend model was used to energy trend in the econometric analysis of this study. Granger causality analysis results show that one-way causality relation at 5% level of significance towards GDP denoted EC was detected.